PENINGKATAN PEMAHAMAN WARGA MASYARAKAT KELURAHAN TRIMULYO KECAMATAN GENUK KOTA SEMARANG MENGENAI SANKSI TERHADAP ORANG YANG BERTINDAK SEBAGAI KURIR NARKOTIKA - Tri Mulyani; B. Rini Heryanti; Muhammad Iftar Aryaputra (Bajang Institute, 2024)
Narcotics circulation cannot be separated from the role of narcotics couriers as intermediaries. Narcotics dealers are also increasingly adept at involving couriers in their distribution, starting from children, adults, the elderly, women, and even using goods delivery services. Narcotics couriers do not know the dangers and threats of sanctions that ensnare them, as regulated in Law Number 35 of 2009 concerning Narcotics, not only prison sentences, but also the death penalty. There is data that in 2022 there will be 404 death row drug couriers waiting to be executed. The factors behind becoming a courier include economic factors, low education, lack of skills, and the large amount of money generated in a short time from narcotics dealers. Starting from this, it is necessary to provide community service in the form of legal education by formulating the problem, namely the lack of understanding of the residents of Trimulyo Village, Genuk District, Semarang City regarding sanctions against people who act as Narcotics Couriers. The expected target is to increase understanding regarding sanctions against people who act as narcotics couriers, so that every member of society has legal awareness and avoids various legal problems. The service was carried out using lecture methods, direct question and answer, and evaluation by comparing the results of distributing pre-test and post-test questionnaires to increase public understanding. The results of discussions on community service activities showed an increase in understanding of 59%.